2020
DOI: 10.1101/gad.333963.119
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length heterogeneity in ALT cells is maintained by PML-dependent localization of the BTR complex to telomeres

Abstract: Telomeres consist of TTAGGG repeats bound by protein complexes that serve to protect the natural end of linear chromosomes. Most cells maintain telomere repeat lengths by using the enzyme telomerase, although there are some cancer cells that use a telomerase-independent mechanism of telomere extension, termed alternative lengthening of telomeres (ALT). Cells that use ALT are characterized, in part, by the presence of specialized PML nuclear bodies called ALT-associated PML bodies (APBs). APBs localize to and c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
63
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 70 publications
10
63
0
Order By: Relevance
“…BLM depletion strongly attenuated C-circles and reduced STING and RSAD2 induction in HeLa LT cells following TLK depletion ( Figures 6 A, 6B, and S6 A). We next examined U-2-OS cells lacking PML, a key component of APBs that is required for efficient C-circle production ( Figure 6 C) ( Loe et al., 2020 ). Deletion of PML also strongly attenuated RSAD2 induction following TLK1/2 depletion and reduced extranuclear telomeric FISH signal, indicating that ECTR production contributes to innate immune activation in TLK-depleted cells ( Figures 6 D, S6 B, and S6C).…”
Section: Resultsmentioning
confidence: 99%
“…BLM depletion strongly attenuated C-circles and reduced STING and RSAD2 induction in HeLa LT cells following TLK depletion ( Figures 6 A, 6B, and S6 A). We next examined U-2-OS cells lacking PML, a key component of APBs that is required for efficient C-circle production ( Figure 6 C) ( Loe et al., 2020 ). Deletion of PML also strongly attenuated RSAD2 induction following TLK1/2 depletion and reduced extranuclear telomeric FISH signal, indicating that ECTR production contributes to innate immune activation in TLK-depleted cells ( Figures 6 D, S6 B, and S6C).…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that BLM helicase was recruited to synthetic condensates formed by polySUMO and polySIM only when the condensate was SUMO rich ( Min et al , 2019 ). A recent study showed that the presence of PML protein is required for the recruitment of BTR complex to telomeres for ALT telomere maintenance ( Loe et al , 2020 ). It is possible that the chemistry of APB condensates is actively regulated during the course of telomere elongation to selectively recruit different factors based on direct SUMO–SIM interactions or indirect interactions with existing APB components.…”
Section: Discussionmentioning
confidence: 99%
“…PML nuclear bodies are dynamic structures in the nucleus that transiently sequester up to 100 different proteins that are implicated in many cellular functions including tumor suppression, DNA replication, gene transcription, DNA repair, viral pathogenicity, cellular senescence, and apoptosis ( Lallemand-Breitenbach and de The, 2010 ). Inhibiting APB formation by knocking down PML protein, an essential component of PML nuclear bodies, leads to telomere shortening ( Draskovic et al , 2009 ; Osterwald et al , 2015 ; Loe et al , 2020 ), indicating that APBs contribute to ALT telomere maintenance. In addition to typical PML nuclear body components, APBs contain proteins involved in homologous recombination such as replication protein A (RPA), Rad51, and breast cancer susceptibility protein 1 (BRCA1) ( Nabetani and Ishikawa, 2011 ), which suggests that APBs promote telomere synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of the helicase BLM triggered ALT-like phenotypes in presence of these reconstituted APB-like condensates suggesting that concentration of specific DNA repair factors, together with the clustering of telomeres to provide repair templates, are required for induction of the ALT phenotype ( 33 ). Stochiometry of the SUMO-SIM interactions controls recruitment of BLM or of the full BLM–TOP3A–RMI (BTR) complex at telomeric ends in APBs ( 33 , 207 ). The BTR complex is essential for telomere lengthening and its artificial tethering to telomeres can bypass the absence of PML to induce ALT ( 207 ).…”
Section: Pml Nbs Participate In the Regulation Of Cellular Chromatin mentioning
confidence: 99%